The EU's decision traps comparing policies - Falkner, Gerda (Oxford : Oxford University Press, 2011)
Is European integration predominantly characterised by stalemate? 'The EU's Decision Traps' compares a number of crucial EU policy areas discussing if, and how, political blockage can be overcome in the process of European integration.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Comparative government; Europe -- Economic integration